2014
DOI: 10.2217/pme.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenetics of Lopinavir/Ritonavir in Hiv-Infected European Patients

Abstract: Replication analysis should confirm the novel results obtained in this study prior to its application in the clinical practice to achieve a safer LPV/r-based combined antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“… Increased uric acid Ribavirin 2 −/− ITPA (2B: Hemolysis, thrombocytopenia) 1) SLC28A2, SLC28A3, SLC2A1 (PK) 69 Intestinal uptake via CNTs (encoded by SLC ). Hemolytic anemia Lopinavir/ritonavir 34 −/− ABCB1, ABCC1 (3: Efficacy in HIV); ABCC2, SLCO1B (4: PK) 1) CYP3A4, CYP3A5, SLCO1B1, ABCC2, DRD3, MDR1 (PK) 39 , 70 , 71 2) CETP, MCP1, ABCC2, LEP, SLCO 1B3, IL6 (Toxicity) 40 Inactivation via CYP3A4 QT prolongation, CV events, dyslipidemia, liver injury, GI disturbances Darunavir/cobicistat 1 −/− SLCO3A1 (N/A d : PK) Inactivation via CYP3A4 Liver injury, dyslipidemia, sulfonamide allergy Interferon beta-1b 4 −/− IRF6 (3: Liver injury), Various SNPs (3: Efficacy in multiple sclerosis) 1) HLA-DRB1*04, HLA-DRB1*15, rs9272105, rs4961252 (Neutralizing antibody) 42 , 72 Limited data on metabolism/transporter pathways Liver injury, depression, heart failure, leukopenia, flu-like symptoms, and etc. Tocilizumab 33 −/− IL6R, CD69, FCGR3A, GALNT18 (3: Efficacy in rheumatoid arthritis) Limited data on metabolism/transporter pathways Thrombocytopenia, liver injury, neutropenia, rash, hypertension, infection Ruxolitinib 13 −/− Inactivation mainly via CYP3A4 and partly via CYP2C9 Cytopenia, dyslipidemia, infection, liver injury Baricitinib 11 −/− Efflux transport mainly via OAT3 and partly via BCRP and p-glycoprotein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Increased uric acid Ribavirin 2 −/− ITPA (2B: Hemolysis, thrombocytopenia) 1) SLC28A2, SLC28A3, SLC2A1 (PK) 69 Intestinal uptake via CNTs (encoded by SLC ). Hemolytic anemia Lopinavir/ritonavir 34 −/− ABCB1, ABCC1 (3: Efficacy in HIV); ABCC2, SLCO1B (4: PK) 1) CYP3A4, CYP3A5, SLCO1B1, ABCC2, DRD3, MDR1 (PK) 39 , 70 , 71 2) CETP, MCP1, ABCC2, LEP, SLCO 1B3, IL6 (Toxicity) 40 Inactivation via CYP3A4 QT prolongation, CV events, dyslipidemia, liver injury, GI disturbances Darunavir/cobicistat 1 −/− SLCO3A1 (N/A d : PK) Inactivation via CYP3A4 Liver injury, dyslipidemia, sulfonamide allergy Interferon beta-1b 4 −/− IRF6 (3: Liver injury), Various SNPs (3: Efficacy in multiple sclerosis) 1) HLA-DRB1*04, HLA-DRB1*15, rs9272105, rs4961252 (Neutralizing antibody) 42 , 72 Limited data on metabolism/transporter pathways Liver injury, depression, heart failure, leukopenia, flu-like symptoms, and etc. Tocilizumab 33 −/− IL6R, CD69, FCGR3A, GALNT18 (3: Efficacy in rheumatoid arthritis) Limited data on metabolism/transporter pathways Thrombocytopenia, liver injury, neutropenia, rash, hypertension, infection Ruxolitinib 13 −/− Inactivation mainly via CYP3A4 and partly via CYP2C9 Cytopenia, dyslipidemia, infection, liver injury Baricitinib 11 −/− Efflux transport mainly via OAT3 and partly via BCRP and p-glycoprotein.…”
Section: Methodsmentioning
confidence: 99%
“…Clearance of lopinavir in a population PK model was higher in individuals with SLCO1B1*4/*4 and lower in individuals with two or more variant alleles of SLCO1B1*5, ABCC2 or a CYP3A tag compared to the reference group (12.6 vs. 3.9 vs. 5.4 l/h, respectively, p < 0.01) 39 . Another genetic association study explored 290 variants for their effects on lopinavir/ritonavir related toxicity among 104 Caucasian patients with HIV; variants in the CETP, MCP-1, ABCC2, LEP, and SLCO1B3 genes were associated with dyslipidemia and hyperbilirubinemia, and a variant in IL-6 was associated with diarrhea (all p < 0.01) 40 .…”
Section: Azithromycinmentioning
confidence: 99%
“…A latency period of 1 month or longer is common, which may make this a less relevant feature in the treatment of SARS-CoV-2.. There are genetic variations (polymorphisms) across patients, such as a loss-of-function of CYP3A4 [80], that can make patients more susceptible to metabolic toxicities [81]. Screening for these susceptibilities is not practical in the setting of short duration treatment for SARS-CoV-2.…”
Section: Lopinavir-ritonavirmentioning
confidence: 99%
“…GWAS after analyzing 290 variants with the toxicity of LPV/RTV among 104 Caucasian patients with HIV revealed that dyslipidemia and hyperbilirubinemia were significantly associated with some genetic variants of the CETP, MCP-1, ABCC2, LEP, and SLCO1B3 genes. Also, a genetic variant of the IL-6 gene was significantly associated with resulting in diarrhea (all p < 0.01) (Aspiroz et al, 2014;Takahashi et al, 2020).…”
Section: Lopinavir/ritonavirmentioning
confidence: 95%